Bioreactor in the micropropagation of ornamental pineapple - Reis, Caroline Oliveira; Silva, Adriano Bortolotti; Landgraf, Paulo Roberto; Batisita, Jessica Azevedo; Jacome, Guilherme Antonio (Ornamental Horticulture, 2018)
Ornamental pineapple is a hard plant with significant landscaping value. Typically, conventional propagation is performed by clump division with low yields, and may even spread diseases. Plant tissue culture is viable, yielding plants with a high phytosanitary and genetic quality over a short time period. This study aimed to verify the in vitro multiplication of ornamental pineapple plants (Ananas comosus var. bracteatus L.) in different micropropagation systems, in association with BAP concentrations. Plants with about 2 cm were used, transplanted to the different treatments: bioreactor, natural ventilation and conventional micropropagation, combined with 3 BAP concentrations (0, 1 and 2 mg L-1). The basic medium used consisted of MS salts. The highest number of shoots and in vitro culture growth were obtained with the use of bioreactor and culture medium containing 2 mg L-1 BAP. The temporary immersion bioreactor allows air renewal inside the bottles, leading to a better performance of in vitro cultivation of ornamental pineapple, when compared to conventional micropropagation.